2022
DOI: 10.1097/mbp.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of left ventricular outflow tract presystolic wave and 24-h ambulatory blood pressure measurements

Abstract: Objective Left ventricular outflow tract (LVOT) presystolic wave is a novel marker for several cardiac conditions. It is shown to be related to several cardiac conditions. The aim of this study is to investigate the relationship between LVOT presystolic wave and 24-h ambulatory blood pressure measurements.Methods A total of 194 patients who came to the cardiology outpatient clinic were prospectively enrolled in the study. After demographic and clinical inquiry, blood biochemistry and hemogram tests were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The role of the presence of presystolic wave was also assessed in hypertensive patients and it was determined that presystolic waves were an independent predictor associated with subclinical LV dysfunction in this patient subset [6]. Several studies have also reported an association between the presence of presystolic wave and arterial stiffness, systemic hypertension, and non-dipping [15][16][17]. There are also studies investigating potential relationships between coronary artery disease and the lack of presystolic waves.…”
mentioning
confidence: 99%
“…The role of the presence of presystolic wave was also assessed in hypertensive patients and it was determined that presystolic waves were an independent predictor associated with subclinical LV dysfunction in this patient subset [6]. Several studies have also reported an association between the presence of presystolic wave and arterial stiffness, systemic hypertension, and non-dipping [15][16][17]. There are also studies investigating potential relationships between coronary artery disease and the lack of presystolic waves.…”
mentioning
confidence: 99%